Importance of the Penultimate Positive Charge in Mouse Hepatitis Coronavirus A59 Membrane Protein - Verma, Sandhya (American Society for Microbiology, 2007)
The coronavirus membrane (M) protein carboxy tail interacts with the nucleocapsid during virus assembly. Previous studies demonstrated that the two terminal residues are important, and the charged residue (R227) in the penultimate position in the mouse hepatitis coronavirus (MHV) A59 M protein was suggested to participate in intermolecular interactions with negative charges in the nucleocapsid (N) protein. To determine the significance of the positive charge at position 227, we substituted the arginine with lysine (K), aspartic acid (D), glutamic acid (E), or alanine (A) and studied these by reverse genetics in the context of a MHV full-length infectious clone. Viruses with wild-type phenotype were readily recovered with the K or A substitutions. In contrast, negative-charge substitutions were not tolerated as well. In all recovered R227D viruses the negative charge was replaced with heterologous residues resulting from apparent template switching during negative-strand synthesis of subgenomic RNA 7. An additional second-site compensatory V202I substitution was present in some viruses. Recovered R227E viruses had second-site changes within the M protein carboxy tail that were partially compensatory. Significantly, most of the second site changes in the R227E mutant viruses were previously shown to compensate for the removal of negative charges in the N protein. Our results strongly indicate that a positive charge is not absolutely required. It is clear that other regions within the tail must also be involved in helping mediate interactions between the M protein and the nucleocapsid.